Did school characteristics affect the uptake of meningococcal quadrivalent vaccine in Greater Manchester, United Kingdom?. (June 2019) - Fletcher, R.; Wilkinson, E.; Cleary, P.; Blagden, S.; Farmer, S.
Abstract: Objectives: The objective of this study was to assess if school characteristics were associated with the uptake of the meningococcal ACWY (MenACWY) vaccine in Greater Manchester in 2017/18. Study design: This is an ecological cross-sectional study. Methods: We analysed data on all 129 schools in seven local authorities in Greater Manchester from the Department for Education and from local child health information systems to determine whether school characteristics, including school type and Ofsted effectiveness score, were associated with vaccine uptake. Schools with no eligible pupils were excluded. We undertook single-variable and multivariable analysis and considered key interactions. Results: The overall uptake rate was 80.7%, with a median uptake per school of 80.6% (interquartile range, 69.0%–87.4%). Lower vaccination rates were associated with lower overall effectiveness scores (odds ratio [OR]: 3.54, 95% confidence interval [CI]: 3.00–4.19) and lower numbers of pupils eligible for vaccination (OR: 1.39, 95% CI: 1.28–1.51). Schools with a lower percentage of pupils for whom English is a second language and high deprivation were associated with lower uptake (OR: 1.58, 95% CI: 1.41–1.78). In addition, community schools (the schools with the most local authority oversight) had lower vaccination rates than other categories of schools. Conclusions: In this study, uptake rates of the MenACWY vaccine were associated with all five school characteristics considered. Effectiveness scores for schools had the largest association with vaccine uptake, with poorer schools having lower uptake. These characteristics should be used by vaccination providers to prioritise their interventions to increase immunisation rates. Highlights: Uptake rates of the new meningococcal ACWY (MenACWY) vaccine vary between schools. Influence of school characteristics on MenACWY vaccine uptake was unknown. Uptake rates were found to be associated with five school characteristics. These characteristics included school type and Ofsted effectiveness score. Targeting resources on schools with these characteristics may increase uptake.